Writing For Inclusion: strategie educative e processi di inclusione del Progetto Erasmus WIN - Certini, Rossella (Studi sulla Formazione/Open Journal of Education, 2021)
The paper presents the “state of the art” of the European Erasmus KA2 WIN project: Writing for Inclusion. After the introduction, dedicated to the themes of inclusion, from a pedagogical, anthropological and historical point of view, there are several in-depth studies dedicated to inclusive processes at school and in extra-school social contexts. Inclusion is not considered exclusively as the inclusion of disability in educational and work contexts, but it is considered as a transversal practice that we hope will become modus operandi in every daily experience, both individual and collective. This is a first article that presents the work already done within this Erasmus KA2 project and other future essays are expected to deepen and refine the topic.